2018
DOI: 10.24127/bioedukasi.v9i2.1605
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Model Pembelajaran Course Review Horay Terhadap Hasil Belajar Biologi Dan Motivasi Siswa Kelas X Sma Negeri Jayaloka

Abstract: The problem in this study is whether the learning outcomes and motivation biology class X SMA Jayaloka after applied learning model significantly Course Review Horay completely and increased? The method used in this study is quasi-experimental. The population is all students of class X SMA Jayaloka Academic Year 2016/2017. Sampling was carried out by random sampling study for every class has the ability and opportunity are relatively similar and was selected as a sample is a sample class as a class X.3. The da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
1
5
0
1
Order By: Relevance
“…Learning with the CHR model attracts and encourages students to be able to involve directly and trains student cooperation, so the theory delivery will not be monotonous. Consequently, it can attract the students' attention and increase their motivation to focus on the lesson (Triyanti et al, 2018). With this learning model, the students will be stimulated to hone their problem-solving abilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Learning with the CHR model attracts and encourages students to be able to involve directly and trains student cooperation, so the theory delivery will not be monotonous. Consequently, it can attract the students' attention and increase their motivation to focus on the lesson (Triyanti et al, 2018). With this learning model, the students will be stimulated to hone their problem-solving abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Learning with the CHR model attracts and encourages the students to be able to go directly into it and it trains the student cooperation so that the theory delivery will not be monotonous. Finally, it can attract the students' attention and increase their motivation to focus on the lesson (Triyanti, Harmoko, & Lestari, 2018). Because it can enhance students' thinking abilities, this learning model has a favorable effect on the learning process.…”
Section: Introductionmentioning
confidence: 99%
“…This is because, in its application, students who can answer the questions correctly will be directed to shout the word "hooray" or other agreed yells. Previous studies have revealed that the course review horay learning model can improve the learning atmosphere (Triyanti et al, 2018). Other findings also reveal that the course review horay learning model improves learning outcomes (Antari et al, 2019;Rangkuti & Rangkuti, 2019).…”
Section: Introductionmentioning
confidence: 94%
“…In the 21st century, writing skills greatly influence how well students write in class. Students' writing skills can be improved by writing essays based on factors such as content that is appropriate to the topic, systematic content, correct word choice, sentence effectiveness, and the use of enhanced spelling (EYD), including the use of capital letters and proper punctuation (Jultia et al, 2019;Triyanti et al, 2018). Exercises or practices often carried out in class, and the field can help improve writing skills.…”
Section: Introductionmentioning
confidence: 99%
“…Menurut Sari (2015) Model pembelajaran CRH dapat menciptakan suasana kelas menjadi meriah dan menyenangkan karena setiap peserta didik yang sudah mendapat tanda (v) vertikal atau horizontal atau diagonal harus berteriak horay atau yel-yel lainnya. Menurut Triyanti (2018) dengan model pembelajaran Course Review Horay diharapkan siswa lebih semangat dalam belajar karena pembelajarannya tidak monoton diselingi sedikit hiburan sehingga suasana tidak menegangkan. Selain itu pembelajarannya menarik dan mendorong siswa untuk dapat terjun langsung ke dalamnya serta melatih kerjasama siswa dengan begitu penyampaian teori tidak akan monoton, sehingga dapat menarik perhatian siswa dan meningkatkan motivasi siswa untuk fokus pada pelajaran tersebut.…”
Section: Pendahuluanunclassified